OSH Management in Small and Medium Enterprises: A Bibliometric Review - Sofia Afifah Hazemi; Noor Diana Abdul Majid; Mirta Widia; Hanida Abdul Aziz (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2025)
Sustainable Small and medium-sized enterprises (SMEs) are crucial to economic growth but face significant challenges in occupational safety and health (OSH). SMEs often lack the resources, expertise, and institutional support needed to manage OSH effectively, leading to higher rates of workplace accidents. This study addresses the lack of thematic synthesis and trend forecasting by offering a structured overview of the field's intellectual landscape. Using bibliographic coupling and co-word analysis, we identified key research themes, emerging trends, and influential studies. Data were collected from the Web of Science (WoS) Core Collection (1990 to 2024) yielding 552 initial records. After screening, 393 journal articles were analysed, with a total of 6,408 citations (6,181 excluding self-citations), an average of 16.31 citations per item and an H-index of 39. Applying a 30-citation threshold, 54 highly cited papers were subjected to bibliographic coupling, revealing six thematic clusters. The analysis indicates four prominent clusters: (1) the role of human resources in OSH programs, (2) health certifications and safety management systems, (3) employee perceptions of OSH efforts, and (4) the development of OSH models tailored to SMEs. Consequently, our findings demonstrate that OSH research in SMEs is steadily evolving toward more integrated, systematic management approaches. These insights suggest that enhancing OSH outcomes requires targeted strategies including strengthening human resource roles, adopting formal safety frameworks, emphasizing risk assessment and staff training, and implementing standardized practices fit for the SME context.